Rene Bibaud's Complete fundamentals of rope jumping [a teaching guide] - Bibaud, Rene; Henness, Gregg; Johns, Chris; Human Kinetics (Organization) (Illinois : Human Kinetics, 2007)
This program takes trough eight sets of skill breakdowns, including single-rope skills, long-rope activities, group routines, build-ups for double dutch, and fun games
Title from title screen
Instructor: Rene Bibaud
Ages 7-11
Keywords: Rope skipping; Physical fitness; Exercise for children